2011
DOI: 10.1007/s11832-011-0342-6
|View full text |Cite
|
Sign up to set email alerts
|

Fusionless procedures for the management of early-onset spine deformities in 2011: What do we know?

Abstract: While attempts to understand them better and treat them more effectively, early-onset deformities have gained great pace in the past few years. Large patient series with long follow-ups that would provide high levels of evidence are still almost non-existent. That there is no safe treatment algorithm defined and agreed upon for this patient population continues to pose a challenge for pediatric spine surgeons. In this review, authors who are well known for their research and experience in the treatment of earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 74 publications
(110 reference statements)
1
21
0
3
Order By: Relevance
“…Rod breakage is a main issue with the use of growth rods in patients. However, there is limited literature that sheds light on the failure mechanism [1][2][3][6][7][8]26]. Yang et al [6] found that the risk of rod fracture increases with single rods, stainless-steel rods, and smaller-diameter rods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rod breakage is a main issue with the use of growth rods in patients. However, there is limited literature that sheds light on the failure mechanism [1][2][3][6][7][8]26]. Yang et al [6] found that the risk of rod fracture increases with single rods, stainless-steel rods, and smaller-diameter rods.…”
Section: Discussionmentioning
confidence: 99%
“…Dual growth rods are the most commonly used distraction-based, ''growth-friendly'' surgical instrumentation [1,2]. Growth rods are used to limit the progression of scoliosis without restraining spinal growth.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to quantify the social consequences of the growing rod, the data of 265 patients from 16 international centers were studied [32]. More than 90 % of the patients undergoing growing surgery were found to be \10 years of age, and active treatment to take on average 5 years, which meant patients had the potential to undergo up to 12 procedures during this time frame.…”
Section: Controversiesmentioning
confidence: 99%
“…Early fusion, especially when it includes the proximal thoracic spine, can significantly restrict pulmonary function [8]. Therefore, different growth-friendly techniques have been developed to avoid early definitive fusion of the immature spine [9].…”
Section: Introductionmentioning
confidence: 99%